Health-Related Quality of Life or Quality of Medical Service? Current challenges for family doctors - Kanecki, Krzysztof; Nitsch-Osuch, Aneta; Tyszko, Piotr Zbigniew (Family Medicine & Primary Care Review, 2016)
Maximizing Health-Related Quality of Life (HRQoL) is one of the most important goals in the work of the family doctor. Providing a high quality of medical services (QMS) should be among the most important challenges in primary health care organizations (PHCOs). In practice, these two areas of activity require continuous improvement, and can complement each other and enhance their mutual impact on the health of patients. The objective of this article is to present selected areas of HRQoL and QMS improvement in the practice of a family doctor, which might contribute to patients’ health, to cost reduction, and to a beneficial reposition of a health center within the medical service market. The paper presents proposals for improving HRQoL and QMS through the use of data from questionnaires filled out by patients, through the cooperation of all the people involved in the delivery of medical services, through adaptation of the IT infrastructure to meet the needs of PHCOs, and through improvements in quality as the result of a process model. QMS is of great importance, especially for both consumers and providers of medical services, including PHCOs. Improvement in quality should be considered as operating on both HRQoL and QMS. This paper presents strategies for selected areas that may contribute to improving QMS, both with respect to the opinions of patients and the functioning of PHCOs.